2001
DOI: 10.1016/s0167-2789(01)00291-3
|View full text |Cite
|
Sign up to set email alerts
|

Resonant flights and transient superdiffusion in a time-periodic, two-dimensional flow

Abstract: Enhanced, passive transport is studied numerically in an oscillating vortex chain with stress-free boundary conditions. The long-range transport is found to be diffusive in the long-time limit with an effective diffusion coefficient D * that peaks dramatically in the vicinity of a few, well-defined resonant frequencies. Superdiffusive transients are also observed for frequencies near these resonant frequencies, with the duration of the transients diverging at the resonant frequencies. Standard analytical techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…For passive particles transport in the flow (16), it has been found that the eddy diffusivity coefficient D eff (ω) displays a complex behavior with resonant-like patterns [39,40], in which the values of D eff (ω) are orders of magnitude larger than the stationary-flow value, D eff (0). The physical mechanism responsible for the resonances is related to the interplay between the oscillation of the separatrices and the circulation inside the cell.…”
Section: Front Speed Dependence On the Frequencymentioning
confidence: 99%
“…For passive particles transport in the flow (16), it has been found that the eddy diffusivity coefficient D eff (ω) displays a complex behavior with resonant-like patterns [39,40], in which the values of D eff (ω) are orders of magnitude larger than the stationary-flow value, D eff (0). The physical mechanism responsible for the resonances is related to the interplay between the oscillation of the separatrices and the circulation inside the cell.…”
Section: Front Speed Dependence On the Frequencymentioning
confidence: 99%
“…and maximum velocity v o . Transport in the oscillating vortex chain (i.e., with v d 0) has been studied extensively [19,20,25,26]; the drift term, however, is new and is added to model ( If v d > v o , transport is typically superdiffusive. In most cases, there are two chaotic regions, separated by an ordered region in the middle of the jet [light blue in Fig.…”
mentioning
confidence: 99%
“…The long-range transport of passive impurities in this system has been studied extensively and is reported on in previous articles. 3,4,6 For the experiments in which a drop of oil is followed, the computer stores only the coordinates of pixels brighter than a user-defined threshold, enabling us to collect data at a rate of 5-10 images per second for several hours (if the drop stays within the visible region) 16,17 .…”
Section: Numerical and Experimental Methodsmentioning
confidence: 99%
“…We define a Lagrangian-generalized Capillary number that is based on finite-time Lyapunov exponents. We then present preliminary results of experimental and numerical studies for the stretching and breakup of drops of oil floating on the surface of a chain of oscillating vortices 3,4 , a flow whose mixing properties have been well-studied 5,6,7 . Statistics of the stretching of the drop are compared with those of the Lagrangian capillary number.…”
Section: Introductionmentioning
confidence: 99%